Occupational Contact Dermatitis in North American Print Machine Operators Referred for Patch Testing: Retrospective Analysis of Cross-Sectional Data From the North American Contact Dermatitis Group 1998 to 2014. Issue 3 (May 2017) - Warshaw, Erin M.; Hagen, Solveig L.; Belsito, Donald V.; DeKoven, Joel G.; Maibach, Howard I.; Mathias, C.G. Toby; Zug, Kathryn A.; Sasseville, Denis; Zirwas, Matthew J.; Fowler, Joseph F.; Fransway, Anthony F.; DeLeo, Vincent A.; et al.
Abstract : Background: Little is known about the epidemiology of contact dermatitis (CD) in print machine operators (PMOs). Objective: The aims of this study were to estimate the prevalence of CD and characterize clinically relevant and occupationally related allergens among PMOs undergoing patch testing. Methods: This was a retrospective cross-sectional analysis of the North American Contact Dermatitis Group data from 1998 to 2014. Results: Of 39, 332 patch-tested patients, 132 (0.3%) were PMOs. Among PMOs, most were male (75.0%) and white (92.4%). The majority were printing press operators (85.6%). The most frequent sites of dermatitis were hands (63.6%), arms (29.5%), and face/scalp (24.2%). More than half had an occupationally related skin condition (56.1%). Final diagnoses were most commonly allergic CD (58.3%) and irritant CD (33.3%). Cobalt (20.8%), carba mix (12.5%), thiuram mix (8.3%), and formaldehyde (8.3%) were the most frequent occupationally related allergens. The top allergen sources included inks (22.9%), gloves (20.8%), and coatings/dye/copy/photographic chemicals (14.6%). Conclusions: Allergic CD, irritant CD, and involvement of exposed body areas were common among PMOs. Common allergens included rubber accelerators, metals, and preservatives.